Characteristics of the Family Caregivers Who Did Not Benefit From a Successful Psychoeducational Group Intervention During Palliative Cancer Care: A Prospective Correlational Study. Issue 1 (January 2017) - Holm, Maja; Årestedt, Kristofer; Carlander, Ida; Wengström, Yvonne; Öhlen, Joakim; Alvariza, Anette
Abstract : Background: Although there has been a steady increase in intervention studies aimed toward supporting family caregivers in palliative cancer care, they often report modest effect sizes and there is a lack of knowledge about possible barriers to intervention effectiveness. Objective: The aim of this study is to explore the characteristics of family caregivers who did not benefit from a successful psychoeducational group intervention compared with the characteristics of those who did. Intervention/Methods: A psychoeducational intervention for family caregivers was delivered at 10 palliative settings in Sweden. Questionnaires were used to collect data at baseline and following the intervention. The Preparedness for Caregiving Scale was the main outcome for the study and was used to decide whether or not the family caregiver had benefited from the intervention (Preparedness for Caregiving Scale difference score ⩽ 0 vs ≥ 1). Results: A total of 82 family caregivers completed the intervention and follow-up. Caregivers who did not benefit from the intervention had significantly higher ratings of their preparedness and competence for caregiving and their health at baseline compared with the group who benefited. They also experienced lower levels of environmental burden and a trend toward fewer symptoms of depression. Conclusions: Family caregivers who did not benefit from the intervention tended to be less vulnerable at baseline. Hence, the potential to improve their ratings was smaller than for the group who did benefit. Implications for Practice: Determining family caregivers in cancer and palliative care who are more likely to benefit from an intervention needs to be explored further in research.